Prospective Assessment of Symptoms to Evaluate Asymptomatic SARS-CoV-2 Infections in a Cohort of Health Care Workers. (14th February 2022) - Goguet, Emilie; Powers, John H; Olsen, Cara H; Tribble, David R; Davies, Julian; Illinik, Luca; Jackson-Thompson, Belinda M; Hollis-Perry, Monique; Maiolatesi, Santina E; Pollett, Simon; Duplessis, Christopher A; Wang, Gregory; et al.
Abstract: Background: The frequency of asymptomatic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections is unclear and may be influenced by how symptoms are evaluated. In this study, we sought to determine the frequency of asymptomatic SARS-CoV-2 infections in a prospective cohort of health care workers (HCWs). Methods: A prospective cohort of HCWs, confirmed negative for SARS-CoV-2 exposure upon enrollment, were evaluated for SARS-CoV-2 infection by monthly analysis of SARS-CoV-2 antibodies as well as referral for polymerase chain reaction testing whenever they exhibited symptoms of coronavirus disease 2019 (COVID-19). Participants completed the standardized and validated FLU-PRO Plus symptom questionnaire scoring viral respiratory disease symptom intensity and frequency at least twice monthly during baseline periods of health and each day they had any symptoms that were different from their baseline. Results: Two hundred sixty-three participants were enrolled between August 25 and December 31, 2020. Through February 28, 2021, 12 participants were diagnosed with SARS-CoV-2 infection. Symptom analysis demonstrated that all 12 had at least mild symptoms of COVID-19, compared with baseline health, near or at time of infection. Conclusions: These results suggest that asymptomatic SARS-CoV-2 infection in unvaccinated, immunocompetent adults is less common than previously reported. While infectious inoculum doses and patient factors may have played a role in the clinical manifestations of SARS-CoV-2 infections in this cohort, we suspect that the high rate of symptomatic disease was due primarily to participant attentiveness to symptoms and collection of symptoms in a standardized, prospective fashion. These results have implications for studies that estimate SARS-CoV-2 infection prevalence and for public health measures to control the spread of this virus.